2010
DOI: 10.1007/s00296-010-1633-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum concentrations of soluble Fas (CD95/Apo-1) and IL-18 in patients with systemic lupus erythematosus

Abstract: Recent researches suggest that imbalance in apoptotic process may lead to susceptibility to systemic lupus erythematosus (SLE). Production of pro-inflammatory cytokines, such as IL-18, has important role in autoimmune process in lupus. There are cumulative data on the pro-apoptotic role of IL-18, in the Fas-mediated apoptosis. Soluble Fas (Apo/1-CD95) is a marker of apoptosis that appears to increase in serum of SLE patients. Previous studies demonstrated increasing serum concentrations of soluble Fas (sFas) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…The results of this study were in line with our previous study, which revealed a strong positive correlation between serum levels of sFas and IL-18 in lupus [12–28] and other studies that demonstrated the impressive action of IL-18 [4, 5, 32, 3638] and sFas [3, 31, 32, 39] in LN. Although we found this positive correlation in both patients with and without proteinuria, this correlation was stronger in LN.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study were in line with our previous study, which revealed a strong positive correlation between serum levels of sFas and IL-18 in lupus [12–28] and other studies that demonstrated the impressive action of IL-18 [4, 5, 32, 3638] and sFas [3, 31, 32, 39] in LN. Although we found this positive correlation in both patients with and without proteinuria, this correlation was stronger in LN.…”
Section: Discussionsupporting
confidence: 93%
“…Chen et al [27] demonstrated the influence of IL-18 on the apoptosis of peripheral blood lymphocytes in adult onset Still's disease (AOSD), SLE, and healthy participants. In our previous study, we also demonstrated that sFas and IL-18 rise in correlation with disease activity in lupus [28]. …”
Section: Introductionmentioning
confidence: 86%
“…This mesangial autocrine growth factor was shown to play a pivotal role in mesangial cell proliferation, which is essential for the progression of various glomerular diseases [ 74 ]. Our study did not confirm IL18 as a useful biomarker to assess the activity of renal disease, as reported by others [ 42 , 43 ]. On the other hand, our results nominated spectrum of novel biomarkers of renal involvement for further confirmation studies.…”
Section: Discussioncontrasting
confidence: 67%
“…Further highly upregulated proteins, IL18 and sulfotransferase 1A1, were already reported in autoimmunity. An elevated IL18 serum level was reported in SLE [ 42 ], especially in LN patients [ 43 , 44 ]. Regarding sulfotransferase 1A1, higher activity was found in autoimmune thyroid disease glands compared to normal thyroids [ 45 ], but no information yet exists in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…S e r u m l e v e l s o f s F a s c o r r e l a t e w i t h p e r c e n t a g e s o f activated B cells but not with that of activated T cells (Bijl, 1998). There is a significant correlation between serum concentrations of sFas and serum IL-18 in SLE patients (Sahebari, 2010). sFas and TNF serum levels are increased in SLE patients (Miret et al, 2001).…”
Section: The Fas/fasl Pathway Of Apoptosis In Slementioning
confidence: 86%